Dylematy i zagrożenia we współczesnym rozwoju regionalnym - Miszczak, Katarzyna (Dilemmas and threats in modern regional development, 2006)
The main aim of this article is an attempt of identification and short description of threats occuring in modem regional development. The author discusses also dilemmas that decision makers and local communities deal with in regions. The achievement of harmonious and complex development taking into consideration principles of integrated socio-economic and spatial-ecological order is the task which realization leads through tensions, contradictions, and conflicts. Activities undertaken in the sphere of regional policy head towards reduction of differences in living standard and economic development between the poorest and the richest regions. Excessive differences are barriers not only to integration and globalization processes butthey are also major obstacles to achieving higher competition’s level. Poland as a country which recently became a member of the European Union has to fulfill a lot of conditions concerning formation and assistance of regional development. Especially, Poland has to meet all of principles and conditions accepted by European countries. Opinions and conclusions were depicted in synthetic form.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 21-33